2014
DOI: 10.1038/ncomms4352
|View full text |Cite
|
Sign up to set email alerts
|

Pod shattering resistance associated with domestication is mediated by a NAC gene in soybean

Abstract: Loss of seed dispersal is a key agronomical trait targeted by ancient human selection and has been regarded as a milestone of crop domestication. In this study, in the legume crop soybean Glycine max (L.) Merr. which provides vegetable oils and proteins for humans, we show that the key cellular feature of the shattering-resistant trait lies in the excessively lignified fibre cap cells (FCC) with the abscission layer unchanged in the pod ventral suture. We demonstrate that a NAC (NAM, ATAF1/2 and CUC2) gene SHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
225
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(237 citation statements)
references
References 63 publications
9
225
2
1
Order By: Relevance
“…A gene responsible for domestication, SHAT1-5 on chromosome 16, has very recently been identified (12). This gene, which is homologous to NST1/2 of A. thaliana, activates secondary cell-wall biosynthesis and promotes the thickening of fiber-cap cells in pod sutures (12), the dehiscence site in soybean pods. SHAT1-5 also enhances pod-wall binding strength.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A gene responsible for domestication, SHAT1-5 on chromosome 16, has very recently been identified (12). This gene, which is homologous to NST1/2 of A. thaliana, activates secondary cell-wall biosynthesis and promotes the thickening of fiber-cap cells in pod sutures (12), the dehiscence site in soybean pods. SHAT1-5 also enhances pod-wall binding strength.…”
mentioning
confidence: 99%
“…Genetic analysis using a mapping population derived from a cross between these two species has not identified any quantitative trait loci (QTLs) with large effects on shattering, suggesting that multiple genes with minor effects contribute to shattering resistance in the cultivated species (11). A gene responsible for domestication, SHAT1-5 on chromosome 16, has very recently been identified (12). This gene, which is homologous to NST1/2 of A. thaliana, activates secondary cell-wall biosynthesis and promotes the thickening of fiber-cap cells in pod sutures (12), the dehiscence site in soybean pods.…”
mentioning
confidence: 99%
“…Examination of the dehiscence zone of soybean pod and the expression analysis of the soybean endo polygalacturonase transcript revealed that the endo polygalacturonase was primarily found in dehiscence-related tissue and was presumably involved in the breakdown of the middle lamella before dehiscence (Christiansen et al, 2002). A study by Dong et al (2014) revealed that the excessively lignified fiber cap cells (FCC) with the abscission layer unchanged in the soybean pod ventral suture as the key cellular feature of the shattering-resistant trait. Meanwhile, Funatsuki et al, (2014) revealed important aspects of pod shattering, namely, the dehiscing force and the associated regulatory gene.…”
Section: Identification For Shattering Resistancementioning
confidence: 99%
“…SHAT1-5 controls secondary cell-wall formation by promoting the lignification of fiber cap cells in pod sutures [94].…”
Section: Shattering In Legumesmentioning
confidence: 99%
“…Genetic analysis of pod shattering has been carried out in various legumes including soybean [48,[93][94][95][96][97][98][99][100][101], common bean [13,44], pea [18,50,102], cowpea [49,[103][104][105][106], lentil [16,46,107], narrow-leaf lupin [47,108], azuki bean [45,109], and common vetch [43,110]. In most of the legumes that have been studied so far, pod shattering is found to be a dominant trait controlled by one or two genes or QTLs (Table 1).…”
Section: Shattering In Legumesmentioning
confidence: 99%